Pengaruh Harga Dan Kualitas Produk Terhadap Kepuasan Konsumen Produk HPAI: The Effect of Price and Product Quality on Consumer Satisfaction of HPAI Products - Rahmatillah, Alfani; Oktiani, Nurvi (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2025)
This research aims to determine the influence of price and product quality on consumer satisfaction of HPAI products. This research is quantitative descriptive, which uses a data collection method in the form of literature studies, interview and questionnaires distributed to 30 respondents in Rawasari urban village with the criteria of having purchased and consumed HPAI products. The sampling technique used in this research is non-probability sampling with a convenience sampling approach. The data obtained was then processed using SPSS to calculate data quality tests, classical assumption tests, hypothesis tests, determination coefficient tests and linear regression tests. The results of the research show that price and product quality simultaneously have a positive and significant influence on consumer satisfaction of HPAI products. However, partially the price does not have a significant influence on consumer satisfaction of HPAI products, while product quality has a significant influence on consumer satisfaction of HPAI products.